Groundwater storage and depletion trends in Tamil Nadu State, India - Chinnasamy, Pennan; Agoramoorthy, G. (Springer, 2015)
Groundwater irrigation is the most predominant method used across India. The south Indian state of Tamil Nadu is one of the largest producers of agricultural products, and is largely dependent on groundwater for irrigation. The impact of increased irrigation due to intensification of agricultural activities on groundwater levels has not been well researched, both spatially and temporally. Hence this study has used remote sensing data from NASA’s Gravity Recovery and Climate Experiment and the Global Land Data Assimilation Systems to assess the total change in groundwater storage across the state of Tamil Nadu over a period of 11 years, from 2002 to 2012. The results show groundwater depletion at the rate of 21.4 km3 yr-1, which is 8% more than the annual recharge rate (19.81 km3 yr-1) owing to the total rainfall of 1016 mm yr1. Maximum depletion was observed in 2008, while the least depletion was observed in 2002 with rates of 41.15 and 0.32 cm yr-1, respectively. Districts such as Dharmapuri, Vellore and Thiruvannamali encountered intense groundwater depletion. Observed spatiotemporal groundwater storage will benefit India’s water resource managers and policymakers for the future management of groundwater resources to enhance food and water security.